Mekanisme Jual Beli Emas Online Melalui Aplikasi (Pluang) Persfektif Hukum Ekonomi Syariah - Syaripudin, Enceng Iip; Mawarni, Ai Hilma (STAI Al Musaddadiyah Garut, 2023)
Pluang is a digital investment application developed by PT Bumi Santosa Cemerlang. Pluang makes it easy for people to invest in gold easily digitally. The price of gold offered in units of 0.01 grams is Rp. 8,638,-. If you want to get a profit from investing in the Pluang application, buying gold must be priced down and resell it at a rising price so that you can profit from selling the gold. This study aims to determine the mechanism of buying and selling gold online in the Pluang application and the view of Islamic economic law regarding buying and selling gold online in the Pluang application. Thus, the researcher hopes that this research can be useful as a reference for further researchers. This study uses a type of qualitative research with data collection techniques used, namely interviews, documentation and literature study. By collecting actual data and information, this study intends to describe the problem and find the right conclusions. Based on the conclusions from the research results, features such as buying gold, selling gold, repaying gold, and withdrawing gold are available in the Pluang application. In making transactions in the Pluang application based on the DSN-MUI fatwa, the contracts used are Wadiah, Murabahah, and salam contracts. In addition, the view of sharia economic law on buying and selling gold online is legal or permissible as long as it complies with the provisions of Islamic sharia law.